2002
DOI: 10.1093/clinchem/48.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Immunometric Assay Interference

Abstract: Background: The primary aim of the study was to reduce interference in an in-house two-site, two-step immunometric assay. Methods: In the running laboratory routine, 11 261 samples were tested with a carcinoembryonic antigen (CEA) assay with bovine immunoglobulin but no murine immunoglobulins in the buffer, in parallel to our routine CEA assay, using 15 mg/L heat-treated nonspecific murine immunoglobulin (MAK33) in the buffer and with the Fc fragments removed from the capture antibody. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 36 publications
1
57
0
1
Order By: Relevance
“…The frequency of interference in canine samples for the AMH Gen II assay is most likely considerably lower than the 9% reported in the screening of canine anti‐mouse antibodies since only two of the seven evaluated samples caused erroneous results. This data are consistent with larger cohort (>10 000 samples) studies of human samples submitted for immunoassay analysis, which estimate the frequency of interference to 0.03%‐4% …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The frequency of interference in canine samples for the AMH Gen II assay is most likely considerably lower than the 9% reported in the screening of canine anti‐mouse antibodies since only two of the seven evaluated samples caused erroneous results. This data are consistent with larger cohort (>10 000 samples) studies of human samples submitted for immunoassay analysis, which estimate the frequency of interference to 0.03%‐4% …”
Section: Discussionsupporting
confidence: 89%
“…Increasing the MAK33 concentration to 1.0 mg/mL decreased the AMH concentrations by 57% for serum 1, and normalized the result from 5.71 to < 0.714 pmol/L in serum 2. Although the mechanism is not fully understood, aggregated antibodies have previously been shown to be superior blockers compared with native IgG . In the same study, it was also seen that 1.0 mg/mL heat‐aggregated MAK33 failed to normalize mouse IgG concentrations in only 1 out of 76 human patient samples with heterophilic antibodies.…”
Section: Discussionmentioning
confidence: 84%
“…14 Some studies have shown that interfering endogenous antibodies are present in up to 30 -40% of patient samples 77 but estimates vary widely. 96,97 A recently published report, however, suggests that interfering antibodies of various types only produce clinically discrepant results in about 0·5% of immunoassays, 14 although others have reported higher 16,98 and lower percentages. 87 Even with such low prevalence, the significance of interference must be appreciated within the many millions of immunoassay tests that are performed every year.…”
Section: Anti-animal Antibodiesmentioning
confidence: 99%
“…Antigen Effect Authors Passive protection in rainbow trouts Lee et al [116] estimates of the prevalence of assay interference by heterophilic antibodies range from 1 to 80% [161e166]. A more thorough analysis of over 11,000 sera in an anti-CEA assay format revealed that about 4% of the results were potentially false [167]. Approaches to eliminate heterophilic antibody interference include the removal or inactivation of interfering immunoglobulins, e.g.…”
Section: Diseasementioning
confidence: 99%
“…Approaches to eliminate heterophilic antibody interference include the removal or inactivation of interfering immunoglobulins, e.g. by precipitation with PEG [168], the use of various buffer additives [167], or the modification of assay antibodies by proteolytically removing of Fc fragments [167,169]. It is unlikely, however, that a single method can resolve these problems [170].…”
Section: Diseasementioning
confidence: 99%